Dermatomyositis as a paraneoplastic syndrome of malignant melanoma or incidental coexistence? - Magdalena Krajewska; Hanna Bartosik; Wojciech Krajewski; Agnieszka Hałoń; Marian Klinger (Termedia Publishing House, 2016)
Introduction . Dermatomyositis is a rare systemic disease of connective tissue characterized by inflammation of the muscles and the skin. Malignant melanoma is a cancer that begins in melanocytes in the skin, mucosa of the rectum, intestine, oral cavity, external genitalia or in the eyeball. Objective . Presentation of a patient with dermatomyositis as a possible paraneoplastic syndrome of malignant melanoma. Case report . We present a case of a 56-year-old woman who was referred to us due to erythematous skin lesions on the limbs, face, neck and upper chest. The patient also complained of progressive muscle pain and weakness of the shoulder and pelvic girdle as well as of dysphagia. The patient had a small ulcerative lesion on the right foot that was removed. Histopathological evaluation revealed malignant melanoma cells, which were also present in the sentinel lymph node. Conclusions. Screening in dermatomyositis patients should also be focused on melanoma, especially in cases with negative antibodies.